Effectiveness of BRILink service in enhancing financial inclusion and wellbeing in East Nusa Tenggara - Situmorang, Resvina; Sanga, Marianus Hendrilensio (Institute of Computer Science (IOCS), 2024)
This study examines the relationship between the effectiveness of BRILink services on financial inclusion and financial wellbeing. In addition, we examined the effects of mediation where financial inclusion is treated as a mediator in this model. This study used a specific sampling method known as purposive sampling and a sample size of 101 participants from East Nusa Tenggara Province. The data was collected through a google forms questionnaire from June 24 to July 23, 2024 and distributed online among BRILink users. Analyze the data using the PLS (partial least squares) technique from SmartPLS 3. The results show that the effectiveness of BRILink services has a positive and significant effect on financial inclusion and financial wellbeing. Financial inclusion does not function to mediate the effect of the effectiveness of BRILink services on the financial wellbeing of the community. The implication is that improving the quality of financial services and financial education is more important to improve the financial welfare of the people of NTT than simply expanding access to financial services.